2016
DOI: 10.1007/s12671-016-0583-z
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Temporal Binding in Meditators

Abstract: We investigate conditions in which more accurate metacognition may lead to greater susceptibility to illusion and thus conditions under which mindfulness meditation may lead to less accurate perceptions. Specifically, greater awareness of intentions may lead to an illusory compression of time between a voluntary action and its outcome (“intentional binding”). Here, we report that experienced Buddhist mindfulness meditators rather than non-meditators display a greater illusory shift of the timing of an outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Differences in the magnitude of intentional binding are often considered to reflect differences in the sense of agency (e.g., Caspar, Christensen, Cleeremans, & Haggard, 2016; Khalighinejad, Di Costa, & Haggard, 2016; Lush, Parkinson, & Dienes, 2016), but this relationship is not straightforward. It has been demonstrated that causal relationships similarly influence reports of a temporal interval between two events without any intentional action, provided that a causal relationship between the events is believed to exist ( causal binding ; Buehner, 2012, 2015; Buehner & Humphreys, 2009; Moore, Lagnado, Deal, & Haggard, 2009).…”
mentioning
confidence: 99%
“…Differences in the magnitude of intentional binding are often considered to reflect differences in the sense of agency (e.g., Caspar, Christensen, Cleeremans, & Haggard, 2016; Khalighinejad, Di Costa, & Haggard, 2016; Lush, Parkinson, & Dienes, 2016), but this relationship is not straightforward. It has been demonstrated that causal relationships similarly influence reports of a temporal interval between two events without any intentional action, provided that a causal relationship between the events is believed to exist ( causal binding ; Buehner, 2012, 2015; Buehner & Humphreys, 2009; Moore, Lagnado, Deal, & Haggard, 2009).…”
mentioning
confidence: 99%
“…Specifically, past research showed correlations between intentional awareness and brain activation related to motor preparation for individuals who are assumed to enjoy high levels of internal insight (e.g., meditators; Jo et al, 2015), as well as demonstrated that these differences can affect the implicit sense of agency. A study by Lush et al (2016), for example, found that intentional binding was stronger for experienced meditators who find practicing mindfulness pleasurable, than for controls (Lush et al, 2016). In addition, beliefs in free will have been linked to intentional binding, which is explained in terms of a motivational or cognitive orientation toward the results of action intentions (Aarts and Van den Bos, 2011; Lynn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…IB data were obtained as described in previous studies. 27,34,45 First, we calculated distinct values for the action shift and the tone shift. and alcohol (0.0, 0.4, and 0.6 g/kg), followed by appropriate post hoc pair-wise comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…IB data were obtained as described in previous studies . First, we calculated distinct values for the action shift and the tone shift.…”
Section: Methodsmentioning
confidence: 99%